1-(2,4-diclorofenil)-1H-pirazóis: síntese, análise estrutural e interação com os receptores canabinóides CB1 - Machado, Pablo (2010)
A method to obtain fourteen enones [EtO2CC(O)C(R2)=C(R1)OR, where R = H, Me; R1 = Pr, Ph, 4-MeOC6H4, 4-MeC6H4, 4-FC6H4, 4-ClC6H4, 4-BrC6H4, 4-NO2C6H4, Fur- 2-yl; R2 = H; R1,R2 = -(CH2)3-, -(CH2)4-, -(CH2)5-, -(CH2)6-, 3,4-dihydronaphthalen-2-yl] from acylation of acetals with ethyl oxalyl chloride is reported. The cyclocondensation reaction of these substrates with 2,4-dichlorophenyl hydrazine hydrochloride under ultrasound irradiation furnished a series of 1-(2,4-dichlorophenyl)-3-ethylcarboxylate-1Hpyrazoles in 71-92% yields. The pyrazole ester derivatives with R1,R2 = -(CH2)3-, - (CH2)4-, -(CH2)5-, and (CH2)6- suffered hidrolysis reaction in basic media supplied the carboxylic acids (94-97%) which were converted to the corresponding acid chlorides after reaction with thionyl chloride. The reaction of acid chlorides with primary amines (piperidin-1-ylamine, propylamine, 2-morpholino-4-yl-ethylamine, aniline, 4-metoxiphenylamina, 4-nitrophenylamina) led to respective 3-carboxyamide-1-(2,4-dichlorophenyl)-1H-pyrazoles in 85-97% yields. In addition to spectroscopic data the structure of the compounds was studied by X-ray diffraction experiments. Since, the 3-carboxyamide-1-(2,4-dichlorophenyl)-1H-pyrazoles are structurally similar to Rimonabant, a known antagonist of CB1 receptors, binding assays were performed to the cannabinoid receptor CB1. The most promising ligand and candidate to become prototype was the 1-(2,4-dichlorophenyl)-4,5,6,7,8,9-hexahydro-1Hcycloocta[c]pyrazole-3-carboxylicacid-piperidin-1-ylamide which shifted approximately 100% of [3H]Rimonabant in the tests.